In Situ Synchrotron X‐Ray Diffraction Study of the Rhombohedral‐to‐HT‐Cubic Phase Transformation in Ln6WO12 (Ln = Y, Ho, Er, Yb). Issue 4 (30th December 2013) - Apostolov, Zlatomir D.; Sarin, Pankaj; Hughes, Robert W.; Kriven, Waltraud M.; Vanderah, T.
<x xml:space="preserve">Abstract</x> The high‐temperature rhombohedral‐to‐fcc phase transformation in the Ln6WO12 (Ln = Y, Ho, Er, Yb) system was investigated by thermal analysis and in situ X‐ray diffraction. The process was characterized by thermodynamic, kinetic, and mechanistic criteria, and the role of the rare‐earth cation on the transformation properties trends was evaluated. An atomistic perspective on the accompanying structural change is presented, as well as a characterization of the associated shape and volume changes. A twofold comparison is performed with the similar low‐temperature fcc‐to‐rhombohedral transformation in the same system. One aspect contrasts the structural changes related to each process, manifested by the behavior of the lattice parameters and transformation characteristics. The second concerns the sequence of transformations according to composition and suggests the order of thermal stability of Ln polyhedra in each phase.